School Community Center, A Friendly School For All In Albania - Balla, Nereida (European Scientific Journal, ESJ, 2016)
To improve the quality of work and life in the country's schools, Ministry of Education and Sports has taken the initiative "Schools as Community Centre - A friendly school for all". Minister of Education and Sports, Mrs. Lindita Nikolla, presented this initiative and development incentives, aimed at turning the school into space where it will build a new partnership teacher-family-community. Our legislation on education, the law on university education in the Republic of Albania, the Implementing Provisions of this law, the draft of undergraduate education strategy 2013- 2020, and other documents supporting the functioning of a school open to join decision with family and the community. The concept of community school center, is based on the Convention on the Rights of the Child, and presents a comprehensive approach that links all aspects of education reform in the child's placement in the center of attention in all activities organized and implemented at school. The school as community center, a friendly school for all is an approach (a promotional and developmental movement) to turn the school into the place where the partnership school-familycommunity is built and where it is cooperated to develop the full potential of each student. For more than two decades, Albania developed a number of initiatives which have prepared the society towards the creation of a culture, philosophy, practice and policy in support of child-friendly school which is inclusive and open to the community. It provides the opportunity for the evaluation of school performance regarding the cooperation school-familycommunity and on this basis, strategies to support the establishment of a community school model through cooperation with all stakeholders.